Expanding crossover research: The crossover of job-related self-efficacy within couples - Niessen, Cornelia; Sonnentag, Sabine; Unger, Dana; Neff, Angela (Human Relations, 2013)
This article reports a study that examined the crossover of job-related self-efficacy within working couples, its underlying mechanisms, and its work-related consequences. We proposed that the job-related self-efficacy of one partner (the 'actor') can be transmitted to the other partner (the 'partner'). By building on self-efficacy research (Bandura, 1997), we hypothesized vicarious experience and verbal persuasion to be the mediators underlying this crossover process. We expected that the crossover of job-related self-efficacy would in turn result in the partner's altered engagement at work. Using a sample of 102 professionals with an academic degree and their working partners, we conducted multilevel analyses using the actor-partner interdependence model. Our analyses offered support for our hypotheses. The actor's job-related self-efficacy related positively to the partner's job-related self-efficacy. This relation was mediated by the partner's perceived vicarious experience and verbal persuasion. Additionally, the actor's job-related self-efficacy indirectly related to the partner's work engagement through the partner's job-related self-efficacy. © The Author(s) 2013.